Social Status Differentially Affects Behavioral and Immunological Outcomes of Group-Kept Sows Fed Different Dietary Fiber Using Different Length Feeding Barriers - Pacheco, Eridia; Lopez, Mayra; Salak-Johnson, Janeen L. (Frontiers in Animal Science, 2021)
Aggression is inevitable among group-housed sows even after the social hierarchy is established; however, some sows in the group experience social stress, compromising well-being. This study examined the effects of social status on the well-being of group-housed pregnant sows in pens using a competitive feeding system made from short or long length barriers and fed different high-fiber diets. Thirty-six sows per group were fed gestation diets of either 30% wheat middlings and 15% soybean hulls (MID-SH) or 30% distillers dried grains with solubles and 30% corn germ meal (DDGS-GM) and housed in pens fitted with either short or long barriers resulting in 4 experimental treatments (n = 9 sows/diet-length-block combination): (1) MID-SHshort; (2) MID-SHlong; (3) DDGS-GMshort; (4) DDGS-GMlong. Before moving groups of sows into their treatment pens, sows equally representing all diet-length groups across 4 blocks were subjected to a feeding competition test to calculate dominance values. This subsample of 64 sows remained in assigned treatment groups (n = 16 sows/treatment) until gestational d 108 and was used for analysis. Our results indicate that subordinates' well-being may be improved by housing them in pens with long barriers and feeding fiber-modified diets. More specifically, subordinates in pens with long barriers experienced less aggression and displacements (P < 0.0001) and had heavier weights and gains (P < 0.05), especially those in MID-SHlong treatment. Subordinates in the MID-SHlong also had more eat bouts and less sham-chew bouts (P < 0.05); whereas, subordinates in DDGS-GMshort had fewer bouts of oral-nasal-facial behaviors. Other measures such as cortisol and neutrophil-to-lymphocyte ratio were elevated among dominants in MID-SHlong compared to sows in other treatments (P < 0.05). Glucose was highest among subordinates in DDGS-GMlong, and lowest among dominants in the same treatment (P < 0.05). Other measures were affected by diet or barrier length between dominant and subordinate sows. Collectively, these data imply that dominants or subordinates used different coping mechanisms to adapt to the constraints of the pen environment, indicating that the stress they experienced was different. Moreover, social status is a crucial factor that contributes to variation in individual well-being among group-housed sows.